PERANCANGAN GAME TRADISIONAL MACANAN BERBASIS ANDROID - Ade Pujianto; Saeful Anwar (Universitas Janabadra, 2020)
Macanan is a strategy game originating from Central Java, the game of macanan is played by two people who act as tigers or humans, where the tiger player must set a strategy to eat or eliminate all human pieces while the human player must set a strategy to lock the tiger. In some conditions the player does not have a partner to play the game macanan, therefore we need a computer (AI) which can be used as an alternative gameplay game when there are only opponents to play partners. This research will apply the Minimax algorithm as a game against the computer (AI), this research also adds optimization with alpha beta pruning to increase the level of game or intelligence from the computer (AI) in traditional Javanese macanan games.. Keywords : Game, Minimax, Macanan, AI